2012
DOI: 10.3109/01902148.2012.716903
|View full text |Cite
|
Sign up to set email alerts
|

IL-18 and IL-12 synergy induces matrix degrading enzymes in the lung

Abstract: Interleukin (IL)-18 is a pro-inflammatory cytokine suggested to be involved in the development of pulmonary emphysema and inflammation. Studies involving immunology and cancer have revealed that IL-18 can have synergistic effects with IL-12. We have studied the presence of IL-18 and IL-12 receptors (IL-18R/IL-12R) in the lungs and whether IL-18 and IL-12, alone or in combination, have the ability to initiate the induction of mediators related to the development of emphysema and inflammation. The expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 78 publications
(111 reference statements)
1
6
0
Order By: Relevance
“…Apparently, antiangiogenic effects in these findings may be caused due to IL-18-induced expression of other antiangiogenic cytokines, such as, for instance, IL-12. In accordance with previous findings, Cero et al (2012) observed that administration of recombinant murine IL-18 in mice caused significant elevation of pulmonary mRNA levels of MMP. Jiang et al (2003a) observed significant upregulation of IL-18 gene expression in highly metastatic cell line PLA801D.…”
Section: Interleukin-18supporting
confidence: 92%
“…Apparently, antiangiogenic effects in these findings may be caused due to IL-18-induced expression of other antiangiogenic cytokines, such as, for instance, IL-12. In accordance with previous findings, Cero et al (2012) observed that administration of recombinant murine IL-18 in mice caused significant elevation of pulmonary mRNA levels of MMP. Jiang et al (2003a) observed significant upregulation of IL-18 gene expression in highly metastatic cell line PLA801D.…”
Section: Interleukin-18supporting
confidence: 92%
“…IL-12/IL-18 also induce the release of a unique pattern of cytokines (IL-8, CCL22, CXCL-9, and CXCL10) that is different from the pattern given by other polarizing stimuli such as GM-CSF or IFN-g (1). IL-12 appears to cooperate or act synergistically with IL-18 in the control of intracellular parasite infection of macrophages (7) or bridging innate and adaptive immunity (8)(9)(10). Notably, treatment of differentiated macrophages with IL-12/ IL-18 but not with M-CSF induces the production of IFN-g (5,6,11).…”
mentioning
confidence: 99%
“…While tissue level expression of IL-6 is correlated with increased neutrophil counts, EVLP may wash out the intermediary TNF-α signal. Additionally, IL-12 has been cited as a pro-inflammatory cytokine in the inflammosome pathway(24, 25). Our group has previously demonstrated benefit from IL-12 deregulation through the adenosine 2B pathway in a DCD lung EVLP model (Charles AATS 2016 Submitted JTCVS).…”
Section: Discussionmentioning
confidence: 99%